A systematic review and meta-analysis of the effects of resistance exercise on cognitive function in older adults - Wu, Jun; Huang, Chuanfu (Frontiers in Psychiatry, 2025)
ObjectiveCognitive decline has become a major concern with global population ageing, profoundly affecting quality of life and social participation in older adults. Resistance exercise has recently gained attention as a promising strategy to promote neuroplasticity and mitigate cognitive deterioration; however, evidence from randomized controlled trials (RCTs) remains inconsistent. This systematic review and meta-analysis aimed to evaluate the effects of resistance exercise on cognitive function in older adults and to examine whether improvements vary by age and whether exercise parameters—such as type, duration, session length, and weekly frequency—show dose–response relationships.MethodsPubMed, Web of Science, Cochrane Library, Embase, and Science Direct were systematically searched from database inception to September 2024 for RCTs investigating the effects of resistance training on cognitive function in older adults (≥60 years). Study quality was assessed using the Cochrane Risk of Bias 2 (ROB2) tool, and meta-analyses were conducted using RevMan 5.4 and Stata 17.Results17 RCTs (n =739) met the inclusion criteria. Pooled analyses showed that resistance training significantly improved overall cognitive function (SMD = 0.40, P < 0.05), working memory (SMD = 0.44, P < 0.001), verbal learning and memory (MD = 3.01, P < 0.001), and spatial memory span (SMD = 0.63, P < 0.001), whereas effects on processing speed, executive function, and attention were not significant (P > 0.05). Heterogeneity and publication bias analyses indicated stable and unbiased results.ConclusionResistance exercise exerts selective benefits on cognitive domains in older adults, particularly enhancing overall cognition, working memory, verbal learning, and spatial memory. The magnitude of improvement appears to depend on age and exercise parameters, suggesting a potential dose–response relationship. These findings provide evidence-based guidance for resistance training into cognitive health promotion and rehabilitation programs for ageing populations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023407397.